Service Excellence in University Archive of Universitas Indonesia: A Kanban Approach - Wahid Nurfiantara; Anon Mirmani (Record and Library Journal, 2022)
Background of the study: The increasing number of archive services with the implementation of online archive services. This increase services needs to work with excellence service in university archive. The Kanban method is a potential service management approach. This study examines the application of kanban in university archive services and what needs to be considered for its successful implementation. Purpose: This study aims to evaluate and provide recommendations for improving the implementation of the kanban system in university archive services. Method: This study uses a qualitative method (Action research). Collecting data by direct observation and experience of researchers while work as an archivist. Findings: Kanban method helps service coordinators to more easily monitor archive service requests through the kanban board. It is necessary to determine the WIP according to the capacity of the service team. There is a redundant task basket that needs to be integrated into a single process. Improvement of electronic-based work culture for service division archivists in the application of digital kanban. Conclusion: Improving the quality of university archive services can be done with a kanban approach. Kanban flexibility can be applied to a variety of archive service processes. Periodic evaluation needs to be done so that the applied kanban method is more perfect.